DEHUMANISASI PENERTIBAN SATPOL PP PADA PEDAGANG KAKI LIMA : (Studi di Kawasan Gembong Asih Kota Surabaya) - Maya Dwi Susanti Maya; Sugeng Harianto; Rr Nanik Setyowati (Universitas Halu Oleo (UHO), 2023)
The informal sector such as street vendors (PKL) is an alternative to the work done by urban communities. The proliferation of street vendors is a problem because it disrupts the beauty of urban areas such as Surabaya. In addition, the Satpol PP as a controlling unit,street vendors also often experience conflicts when controlling which leads to dehumanization. This study aims to determine the forms of dehumanization carried out by the Satpol PP, the factors causing the dehumanization actions, and to describe the trading activities by street vendors at the Gembong market, Surabaya. This study uses qualitative methods and Johan Galtung's perspective on violence. Data was collected by observation, interviews, and documentation. The results of this study indicate that the dehumanization actions carried out by the Satpol PP are divided into two, namely physical violence such as beatings and verbal violence such as insults or fights between Satpol PP and street vendors. The Satpol PP as the executor often abuses their duties and authority when carrying out enforcement which leads to chaos. The factors that cause dehumanization during the enforcement process are the socialization of the order that was not conveyed properly and other elements who became provocateurs during the clashes. . The PKL profession is in great demand because it requires minimal capital and does not require creativity.